2012
DOI: 10.1029/2011jd017135
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distributions of some parameters of negative downward lightning flashes based on accurate‐stroke‐count studies

Abstract: This paper presents some parameters of negative cloud‐to‐ground lightning flashes in terms of frequency distribution. All data are based on so‐called “accurate‐stroke‐count studies” from different climatological regions in the world and were already published in the literature with the exception of our measurements. We used GPS synchronized data from two digital high‐speed cameras (at 1–8,000 frames/sec). The parameters considered in this study are: (1) continuing current duration, (2) time intervals between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
8
27
7
Order By: Relevance
“…This is an underestimation when compared to ground truth recordings. For instance, based on ground truth recordings in Belgium, Poelman et al (2013a) found a mean multiplicity for negative flashes of 3.7, while similar multiplicities are found in comparable ground truth studies at different regions (Rakov and Huffines, 2003;Saraiva et al, 2010;Ballarotti et al, 2012). Likewise, the high percentage of single stroke negative flashes is an overestimation with respect to ground truth observations, reporting in general values between 20 and 40 % (Fleenor et al, 2009;Biagi et al, 2007;Poelman et al, 2013a).…”
Section: Multiplicitymentioning
confidence: 86%
“…This is an underestimation when compared to ground truth recordings. For instance, based on ground truth recordings in Belgium, Poelman et al (2013a) found a mean multiplicity for negative flashes of 3.7, while similar multiplicities are found in comparable ground truth studies at different regions (Rakov and Huffines, 2003;Saraiva et al, 2010;Ballarotti et al, 2012). Likewise, the high percentage of single stroke negative flashes is an overestimation with respect to ground truth observations, reporting in general values between 20 and 40 % (Fleenor et al, 2009;Biagi et al, 2007;Poelman et al, 2013a).…”
Section: Multiplicitymentioning
confidence: 86%
“…It is also similar to the results of Saba et al (2010), who found a geometric mean value of 61 ms between successive strokes in a given flash. Ballarotti et al (2012) reported an inter-stroke geometric mean of 64 ms, based on 3147 strokes. These studies support the validity of using a shorter temporal threshold for determining the stroke-flash conversion ratio.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Using a time limit of 500 ms, as used by the NLDN, provides a higher reliability in the resulting flash data but may have erroneously lowered the total number of flashes. Ballarotti et al (2012) conducted an accurate stroke-count study using high-speed cameras (at 1000-8000 frames per second). They suggested using the new term N STF to describe the ratio between the average number of strokes per flash and the average number of ground contacts per flash.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Yair et al (2014), relying on results obtained by "video-multiplicity" studies (e.g. Stall et al, 2009;Saba et al, 2010;Ballarotti et al, 2012), suggested narrowing the stroke grouping criteria, using a distance equal to twice the location accuracy of the LLS (e.g. 2.5 km) an inter-stroke duration of 200 ms and no restrictions about the maximum flash duration.…”
Section: Discussionmentioning
confidence: 99%